Studi Pengaruh Polaritas Arus Pengelasan SMAW dan GTAW Pada Lembaran Stainless Steel Metode Pengujian Impact : Study of the Effect of SMAW and GTAW Welding Current Polarity on Stainless Steel Sheets Impact Testing Method - Fahreza Krisna Nugroho; Muhammad Al Fatih Hendrawan (Universitas Pendidikan Ganesha, 2026)
Welding is a widely used fabrication process in industry to permanently join metallic materials. Welding parameters, particularly current polarity, significantly influence heat distribution during welding which ultimately affects the mechanical properties of welded joints. This study aims to analyze the effect of current polarity in Shielded Metal Arc Welding (SMAW) and Gas Tungsten Arc Welding (GTAW) processes on the impact toughness of SUS 304 stainless steel. An experimental method was employed with variations in welding processes (SMAW and GTAW) and electrode polarities, namely electrode negative (EN) and electrode positive (EP). Impact toughness testing was carried out using the Charpy impact test in accordance with ASTM E23 standards. The results show that current polarity significantly affects the impact toughness of welded joints. The highest impact value was obtained from the GTAW process with electrode negative polarity (EN) at 2.89 J/mm², while the lowest value was observed in GTAW with electrode positive polarity (EP) at 0.71 J/mm². These findings indicate that heat distribution during welding influences microstructural characteristics and the material’s ability to absorb impact energy. Based on the results, GTAW with electrode negative polarity is recommended for applications requiring high toughness in stainless steel welded joints.